Effects of Different Aerosols on the Air Pollution and Their Relationship With Meteorological Parameters in North China Plain - Zhao, Hujia; Gui, Ke; Ma, Yanjun; Wang, Yangfeng; Wang, Yaqiang; Wang, Hong; Dou, Yuanyuan; Zheng, Yu; Li, Lei; Zhang, Lei; Zhang, Yuqi; Che, Huizheng; et al. (Frontiers in Environmental Science, 2022)
Located in East Asia, the North China Plain (NCP) has a severe air pollution problem. In this study, variations in visibility, particulate matter (PM), gaseous pollutants, vertical meteorological parameters, and different types of aerosols and their optical properties were evaluated during an air pollution episode that occurred from 10 to 15 January 2019 in Tianjin over the NCP. The visibility was <10 km for approximately 96 h, and the concentrations of PM with an aerodynamic diameter of <2.5 μm (PM2.5) and <10 μm (PM10) increased to 300 and 400 μg/m3, respectively. Because of the conversion of SO2 to sulphate aerosol particles, the sulphur dioxide (SO2) concentration decreased to a minimum of 10 μg/m3. The continual deterioration of visibility was related to the high relative humidity and the boundary layer of <200 m. The southwest airflow (3.0–4.0 m/s) transported various pollutants from Hebei Province to the NCP. Higher mixing ratios of sulphate aerosols, organic aerosols, and black carbon aerosols were distributed over a 0.5-km-diameter area, and the maximum concentrations were approximately 90, 250–300, and 20 μg/kg, respectively. Higher mixing ratios of dust aerosols and sea salt aerosols were distributed within 1.5 km and 1.0–2.5 km, respectively, and their maximum concentrations were approximately 15 and 9 μg/kg, respectively. The findings are valuable for analysing the relationship between air quality and pollutant transport and dispersion in the NCP.